PEMBENTUKAN KONSEP DIRI ANAK USIA DINI DI ONE EARTH SCHOOL BALI - Putri, Dianingtyas Murtanti (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2012)
We were not born with clear understandings of who we are and what our value is. Communication with others can help us to understand and know who we are. For children at their early age, they are not yet to comprehend who they are, therefore they need someone to help them know who they are through particular others. This paper describes the process of how self-concept is formed during golden age (0-8 yo) through interpersonal communication between teacher and kindergarten students. The method in this research is case study at One Earth School Bali with qualitative approach using in-depth interviewtowards several informants purposively. The results showed that the understanding of the age factor as a volatile mood and playful nature of children, then the method of playing while learning in education as well as interpersonal communication teachers and children to build good relationships were potentially form positive self-concept of children, so children have good self-esteem and self-image. Keywords:  self-concept, interpersonal communication, early childhood, learning while playing